Restorative Justice Policy Model in the Future of Criminal Law - Rudini Hasyim, Rado; Nia Betaubun, Restu Monika; B. Rahail, Emiliana (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Restorative justice as a constructive, creative, self-determined action with assistance and open opportunities for group involvement. Peaceful resolution of criminal cases using this mechanism has even been a local wisdom in various regions and customary laws in Indonesia which aims to resolve conflicts, restore balance and bring a sense of peace. As a cultural manifestation, the restorative justice approach should also be realised in practice through the criminal justice system, which has so far seemed rigid. This research focuses on the restorative justice policy model in the future of criminal law. This research is classified as qualitative research with empirical juridical and normative juridical methods oriented to the statutory approach and conceptual approach. This research concludes that restorative justice is a necessity because in addition to international challenges and obligations, it has also become a national trend in the future of criminal law, especially through the New Criminal Code which contains mechanisms for restoring victims’ rights, penal mediation, diversion, supervision punishment and judicial pardon. These mechanisms can operate in various models of informal mediation, traditional village or tribal moots, victim-offender mediation, and reparation negotiation programmes.